2017
DOI: 10.1007/s12031-017-1000-3
|View full text |Cite
|
Sign up to set email alerts
|

G2A as a Threshold Regulator of Inflammatory Hyperalgesia Modulates Chronic Hyperalgesia

Abstract: Tissue injury, pathogen infection, and diseases are often accompanied by inflammation to release mediators that sensitize nociceptors and further recruit immune cells, which can lead to chronic hyperalgesia and inflammation. Tissue acidosis, occurring at the inflammatory site, is a major factor contributing to pain and hyperalgesia. The receptor G2 accumulation (G2A), expressed in neurons and immune cells, responds to protons or oxidized free fatty acids such as 9-hydroxyoctadecadienoic acid produced by injure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In a neuropathic pain model, G2A −/− mice exhibit less mechanical hypersensitivity, however oxaliplatin, the drug used to manifest the model, was shown to increase levels of oxidized lipids which could sensitize TRPV1 via G2A and PKC dependent mechanisms [240]. By contrast, overexpression of G2A in mice reduced mechanical hypersensitivity following CFA-induced inflammation, while knockdown prolonged hyperalgesia [241]. Given that we have recently reported that the CFA model does not result in acidosis, this suggests protons are not agonizing G2A to confer the observed pain relief [55].…”
Section: Proton-sensing G Protein-coupled Receptorsmentioning
confidence: 99%
“…In a neuropathic pain model, G2A −/− mice exhibit less mechanical hypersensitivity, however oxaliplatin, the drug used to manifest the model, was shown to increase levels of oxidized lipids which could sensitize TRPV1 via G2A and PKC dependent mechanisms [240]. By contrast, overexpression of G2A in mice reduced mechanical hypersensitivity following CFA-induced inflammation, while knockdown prolonged hyperalgesia [241]. Given that we have recently reported that the CFA model does not result in acidosis, this suggests protons are not agonizing G2A to confer the observed pain relief [55].…”
Section: Proton-sensing G Protein-coupled Receptorsmentioning
confidence: 99%
“…16 Biological activity of N-acylglycines and oxidized fatty-acids coincides with GPR132 location, in lymphocytes, 17,18 monocyte-lineage cells including macrophages 19 and keratinocytes. 20 GPR132 is implicated in diverse functions including nociception, 21,22 positioning of macrophages at sites of inflamation, 19 haematopoiesis, 23 sensing oxidative stress, 20 regulating macrophage responses in a tumor microenvironment, 24 and microglial colonization from periphery into developing brain (in zebrafish 25 ). However, understanding of GPR132 function has been hampered because multiple other ligands have been published to activate GPR132, and selective pharmacological tools for functional studies have not been available.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced monocyte and macrophage migration due to G2A deletion brought about elevated macrophage recruitment to the vessel wall, as previously reported in Ldlr –/– G2a –/– mice ( Bolick et al, 2007 ). G2A knockdown had also been reported to increase macrophages in mouse neurons and prolong inflammatory hyperalgesia ( Su et al, 2018 ). However, some mice reports stated no change in macrophage chemotaxis by G2A deletion in Ldlr knockouts ( Parks et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%